Finite element analysis on permeability of cut-off wall for landfill - Dai, Guozhong; Xu, Jiajing; Li, Shujin; Li, Xiongwei; Shi, Guicai; Shi, Weicheng (Institute of Advanced Engineering and Science, 2021)
Finite element method is an efficient numerical calculation method based on information technology, which can be used to solve complex equations in various problems. At present, the finite element method is mainly used to deal with seepage problems in dams, while there is less study on seepage in landfill. In this paper, finite element method is used to analyze the seepage of cut-off wall of a landfill in Jiangsu Province, and the movement of landfill leachate in cut-off wall under different conditions is simulated. The simulation results show that The cut-off wall can effectively slow down the seepage velocity of leachate; Under different conditions, the maximum gradient of the cut-off wall are 18.68 and 13.84 respectively, which conforms to Chinese national standard. Therefore, the design of cut-off wall is safe and reasonable, and filtration erosion will not occur; This simulation method combined with information technology can provide new solutions and ideas for other projects to verify safety and rationality.